A rare case of acute myocardial infarction with heart failure following hump-nosed viper bite in a Sri Lankan female - W. M. D. A. S. Wanninayake; Tilan Aponso; Manohari Seneviratne; Dhanapala Dissanayake (Tropical Medicine and Health)
Abstract Background Hump-nosed viper (Hypnale species) bites are an important cause of mortality and morbidity in southern India and Sri Lanka, accounting for 27 and 77% of venomous snake bites, respectively. Previously, we knew them to be moderately venomous snakes, primarily causing local envenomation. However, recent reports have indicated severe systemic envenomation incidents, which include hemostatic dysfunction, microangiopathic hemolysis, kidney injury, myocardial toxicity, and even death. The literature rarely reports cardiac manifestations from hump-nosed viper bites, and all reported cases show cardiac manifestations within hours of the snake bite. The literature did not report late presentations of cardiac manifestations. Here, we report a case of hump-nosed viper bite complicated with type 2 myocardial infarction and acute pulmonary oedema secondary to acute heart failure in a Sri Lankan female presented to the National Hospital of Colombo, Sri Lanka, on day 3 after the snake bite. Case presentation A local hospital transferred a previously healthy 39-year-old female from Kegalle, Sri Lanka, to our hospital for further condition management. We identified the offending snake as a hump-nosed viper after she reported a history of snake bites 3 days ago. She complained of chest tightness on day 3 of the illness and was found to have acute heart failure precipitated by troponin-positive non-ST elevation myocardial infarction in initial investigations. We performed a CT coronary angiography along with a metabolic screening, revealing normal coronary arteries and a negative metabolic screening. Supportive therapy with loop diuretics and oxygen managed her condition, and a follow-up 2D echocardiogram revealed complete recovery of her cardiac function. She was asymptomatic 3 months into the follow-up. Therefore, we concluded that the case was a venom-induced type 2 myocardial infarction leading to heart failure with acute pulmonary oedema, as the CT coronary angiogram showed normal coronary arteries.